Distribution and Significances of the Major Oxides in Recent Coastal Sabkha Sediments of the Al-Dafna Plateau, Northeast Tobruk, Libya - Mohammed, Ahmed. A. (Scientific Journal for Faculty of Science-Sirte University, 2021)
Twenty sabkha samples were chemically analyzed by XRF technique for determination of their major oxides concentrations. Six cores penetrated both the intertidal and supratidal flat zones developed in six wadis mouths in the coastal stretch of the Al-Dafna plateau, northeast Tobruk city. The significance distribution and concentration of the major oxides are discussed and interpreted. Elements in the raw material of the study area reflect important evidence of geochemical weathering processes that affecting parent rocks as well as conditions of sedimentation, and rate of deposition. Correlation coefficients have been used to illustrate the abundance and distribution of these elements. The distribution of major oxides are follows Si2O > CaO > LOI > Al2O3 > SO3 > MgO > Na2O > K2O. The vertical distribution of major elements is mainly controlled by the abundance and proportions of the clastics, carbonates and evaporite minerals. It was found that silica present in the form of detrital, subrounded to rounded silt- to sand-sized quartz grains, while the content of Al2O3 is associated with terrigenous argillaceous materials. On the other hand, the presence of Fe2O3 is related to the abundance of clastic materials in sabkha deposits. It was found that K2O and Na2O concentrations increase toward the sabkha surfaces.